(untitled) (Academicia Globe: Inderscience Research, 2021)
This article discusses the reasons for the importance of supporting small and private entrepreneurship, as well as specific economic methods, mechanisms and incentives. The concept of "economic mechanism" used in practice today has been redefined by the author based on the analysis of scientific views and the results of scientific research.